Analisis Penerapan Manajemen Risiko dalam Meminimalisir Fraud pada PT. Bank Sumut Syariah Kantor Cabang Pembantu Karya - Syofiah Harahap (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to find out how risk management is implemented to minimize fraud at Bank Sumut Syariah Karya sub-branch office. Fraud is a deviant act carried out by parties within the bank or outside the bank with the aim of taking advantage of themselves or a certain group of groups, this is the background to the importance of implementing good and correct risk management to reduce acts of fraud. This research uses a qualitative descriptive approach. The data collection technique was carried out using triangulation (a combination of observation, interviews, documentation). The data in the research is secondary data obtained from various references, including OJK regulations. books, journals and so on. Then analyze it through data reduction, triangulation, and making conclusions. The research results show the form of fraud risk in the financing, operational and compliance processes at PT. Bank Sumut Syariah Karya sub-branch office, namely, guaranteeing collateral that does not belong to prospective customers in the financing process, employee errors in filling in the customer's ATM nominal that occur during the operational process and employees who violate/violate existing rules in the company as one form of risk that arises. occurs at compliance risk. Factors causing fraud at PT. Bank Sumut Syariah sub-branch office works, namely: Governance system, lack of supervision, and employee integrity. Implementation of risk management at PT. Bank Sumut Sayariah Karya sub-branch office has implemented well the standards set by POJK No.65/POJK.03/2016 article 3 concerning the implementation of risk management for sharia commercial banks and sharia business units, through several stages, namely: risk identification, Risk measurement, risk monitoring, and risk control.